Immunization status of children admitted to a tertiary hospital in India - Natu, Sanjay Anil; Mhatre, Sameer; Shanbhag, Rachna; Captain, Mustafa; Kulkarni, Ketaki (International Journal of Contemporary Pediatrics, 2020)
Background: In spite of the ongoing Universal immunization program (UIP), National family health survey data shows declining trend in the number of children fully immunized in Maharashtra. Hence this study was undertaken to determine immunization status in 12-23 months age children admitted to pediatric wards of a tertiary care hospital and factors affecting it. Methods: A prospective, cross sectional study was carried out in which children between 12-23 months age admitted to paediatric wards of a tertiary care hospital were included. Immunization history for Universal immunization program vaccines and socio-demographic information was collected and analysed to find the immunization status and its correlation with various demographic factors. Results: Of total 418 children, 70.3% were completely immunized, 27.8% incompletely immunized and 1.9% unimmunized. Majority were immunized in government centers. 83.3% subjects were of 1st/2nd birth order, 90.4% were delivered institutionally and 76.1% were delivered vaginally. Around half of the children’s fathers and mothers were illiterate. Only father was employed in 75.4% while both parents were employed in 23.4%. Birth order, place of delivery, mode of delivery, father and mother’s education and employment status were statistically associated with immunization while gender, presence of immunization card, migrant status and place of immunization were not associated. Reasons for incomplete immunization included lack of knowledge about immunization and ‘child not well’ at time of immunization. Conclusions: Even in a population with health seeking behaviour almost one third of the children were incompletely immunized. Special efforts are required for finding groups of children with high chances of being incompletely immunized.